Penerapan Peran Orang Tua dan Guru dalam Pencegahan Stunting melalui Pendampingan Parenting di SDIT Cahaya La Royba - Indra Martha Rusmana; Jaka Wijaya Kusuma; Hamidah Hamidah; Amyati Amyati; Aris Trismayadi Nurizki (Gapenas Publisher, 2022)
Stunting problems become a conflict that needs to receive focused attention. Stunting cases are still ups and downs, this is due to parenting and residents' understanding of stunting is still low. The purpose of community service is to provide assistance and strengthening of citizens to have the ability to prevent stunting. The results of this community service are needed to be able to foster awareness of the causes of stunting conflicts in each family and will remind each other which eventually as a movement that synergizes with each other. Methods are carried out by creating or seeking the art of stunting prevention management, planning preventive actions, socialization and application in the family. Conveying understanding to teachers and parents related to stunting means that important things and sharing interactions needed will be a routine and periodic activity.